Tectonic and magmatic factors of Li-F granites localization of the East of Russia - Viktor I. Alekseev (Записки Горного института, 2021)
We have investigated tectonic and magmatic factors of Li-F granites localization of the East of Russia. The study is based on the ideas of Far Eastern geologists about the deep structures of intraplate activity. A model of a source structure with mantle heat sources and ore-forming magmatic complexes was used. We carried out a special metallogenic analysis of the East of Russia as applied to the rare metal-tin-bearing formation of subalkaline leucogranites, including Li-F ones.